TINGKAT STRES DENGAN POLA MENSTRUASI PADA WARGA BINAAN WANITA DI LEMBAGA PEMASYARAKATAN KLAS IIA YOGYAKARTA - , ZUMIRA FASTAWA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Female inmates represent a specific population suffering different stress levels due to various sources. In addition to the arrest-related depression, they are more likely depressed due to the stressful events of life in the past such as violence and economic difficulties. Stress can influence all aspects of oneâs life, one of which is menstrual cycle disorder. Objective: To find out difference in stress levels due to menstrual cycle disorder among female inmates in the Prison of Class IIA, Yogyakarta. Method: This was a non-experimental analytical quantitative research with crosssectional design. It was conducted from January to March, 2014, with 31 subjects of study. The data were collected using the questionnaire of Social Readjustment Rating Scale and Menstrual Cycle Diary and analyzed using one-way Anova test and unpaired t-test. Result: From the one-way Anova test, difference in average stress levels among the respondents between the groups with the menstrual cycles of <24, 24-35, and >35 days indicates that p-value was >0.05 (p=0.677), so it can be concluded that there was no difference between the groups compared in the study. From the unpaired t-test, difference in average stress levels among respondents between the groups with the menstrual durations of 3-7 and >7 days indicates that p-value was >0.05 (p=0.746), so it can be concluded that there was no difference in average stress levels based on menstrual duration. Conclusion: There was no significant difference in average stress levels based on menstrual cycle among female inmates in the Prison of Class IIA, Yogyakarta.